An Experimental Investigation and Comparative Evaluation of Production Line Balancing Techniques - Mastor, Anthony A. (Management Science, 1970)
Although computationally feasible optimizing algorithms for solving the production line balancing problem have not been found, a number of computational techniques have been devised and used to obtain solutions which are not necessarily optimal solutions but are hoped to be good solutions. In the study the most prominent of these techniques are examined and compared by applying them to a sample of production line balancing problems. The maximum output rate attained for a specified line length is used as the measure of effectiveness and the computing time required to make line balancing calculations for a specified output rate is used as the measure of cost. The central results of the study show that there are significant differences among the effectiveness results achieved by the line balancing techniques. Although the differences are not large, there are few changes in the relative effectiveness of the computing techniques over the range of line lengths, partial ordering strengths, and problem sizes that were investigated. For the larger problems the computing time differences are significant and in some instances are a more important consideration in the relative evaluation of the computing techniques than are the effectiveness results.